The influence of particle size on the mechanical performance of epoxy coir composites (Journal of the College of Basic Education, 2022)
Recently, the employment of agro waste materials as reinforcement for polymersis considered asa milestone on preparing polymer composites. Thiswork is focusing on preparing natural fibers composites and studying theirmechanical performance afterwards. Coir particles are considered as a low cost natural fibres material which can be used as a filler with Epoxy resin matrices. The weight fraction of coir fibres in epoxy resin was 10.0 wt.% with different grain size of (950, 750,250)µm.Hand lay -up method was used to prepare composites of Epoxy reinforced with coir particles. Mechanical properties of Compression and Hardness were examined. Scanning electron microscope (SEM) was utilized to investigate the fracture of fibres and their de-bonding afterwards. Results showed that the Brinell hardness was increased in parallel with the decrease in particle size, while compression strength findingsshowed different behaviour represented bygradual increment that was associated with the increment of particle size.